PENGARUH PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Kurnia Sari; Desy Ismah Anggraini (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to examine and analyze the effect of Profitability, Institutional Ownership, and Company Size on Earnings Management (Study of Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange for the Period 2018 – 2020). The sampling technique used in this study is the purpose sampling method and obtained 57 company data as samples. The data is taken through the financial statements of companies in the consumer goods sector listed on the IDX. This study uses multiple linear regression analysis techniques with the help of SPSS 25 program. The results of this study indicate that profitability has no effect on institutional ownership earnings management and firm size has a significant effect on earnings management. Simultaneously, profitability, institutional ownership and firm size have a significant effect on earnings management.